Pengaruh Pembelajaran SiMaYang dalam Meningkatkan Sikap Kreatif Siswa pada Materi Larutan Elektrolit dan Non Elektrolit - Fitry Ledyani; Sunyono Sunyono; Ratu Betta Rudibyani (Universitas Lampung, 2019)
The research aims to describe the influence of the SiMaYang learning model in improving students' creative attitudes to electrolyte and non-electrolyte solution materials. The method of this research is quasi-experimental with pretest posttest control group design. The population in this study were all students of class X IPA High School Bandar lampung. The sample selection was done by cluster random sampling so that the class X IPA 2 was obtained as the experimental class and class X IPA 4 as the control class. The results showed that differences in the two n-Gain creative attitudes of students in the experimental class had high criteria. The size of the influence of the SiMaYang learning model which has the results as